dataWASHES - Towards an Application Programming Interface of WASHES proceedings data - Araújo, Allysson Allex; Farias, Isaac; Gonçalves, Victor; Santos, Rodrigo; Viana, Davi; Steinmacher, Igor (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES), 2024)
In recent years, there has been an increase in open science initiatives in Software Engineering research, highlighting the relevance of knowledge sharing. This paper embraces this scientific movement by introducing dataWASHES, an open source Application Programming Interface (API) that aims to facilitate streamlined programmatic access to the Workshop on Social, Human, and Economic Aspects of Software (WASHES) proceedings. By alleviating the manual data retrieval challenges and burden, dataWASHES seeks to foster collaboration and enhance research efficiency within the WASHES community. The paper delineates our API’s design, implementation, and impact on WASHES knowledge exchange. Our primary contribution lies in offering a systematic tool for accessing and analyzing WASHES proceedings data, with the potential to pave the way for other research communities that eventually share a similar interest.